Relationship between Diurnal Variation in Intraocular Pressure and Central Corneal Power. Issue 1 (13th January 2023) - Biswas, Sayantan; Biswas, Partha
ABSTRACT: SIGNIFICANCE: Relationship between intraocular pressure (IOP) change and central corneal curvature is complicated by measurement techniques and corneal biomechanical parameters. Findings from this study indicate that it is worthwhile to observe the association between diurnal change in IOP and corneal power. PURPOSE: This study aimed to investigate the relationship between the diurnal change in IOP and central corneal power among eyes with and without myopia. METHODS: Sixty healthy eyes of 24 emmetropes and 36 myopes were recruited for this cross-sectional study. Both anterior and posterior central corneal powers of the steep (Ks), flat (Kf), mean meridian (Km), best-fit spheres, and central corneal thickness were recorded followed by the IOP (Goldmann-correlated IOP [IOPg] and corneal-compensated IOP) and corneal biomechanics (corneal hysteresis and corneal resistance factor). Measurements were obtained every 3 hours from 9.30 am to 6.30 pm . Linear-mixed model was used to determine the relationship between the change in IOP and the associated change in corneal measurements (adjusted for age, sex, refractive error, central corneal thickness, and biomechanics) among the myopic and nonmyopic eyes. RESULTS: Group mean, amplitude of change, and the diurnal change in IOPg were (mean ± standard deviation) 15.14 ± 2.50, 3.33 ± 1.44, and 1.81 ± 1.25 mmHg, respectively. Overall, an IOP increase was associated with a decrease in the adjusted anterior corneal powers. Myopic eyes were associated with a decrease of 0.04 D (95% confidence interval [CI], 0.07 to 0.01 D; P = .02) in Ks and 0.03 D (95% CI, 0.06 to 0.001 D; P = .047) in Kf per mmHg increase in IOP, whereas for emmetropes, per mmHg increase in IOP only flattened the Kf by 0.03 D (95% CI, 0.06 to 0.004 D; P = .02). CONCLUSIONS: Change in anterior corneal power was inversely related to the change in IOPg, with myopic and nonmyopic eyes reporting a significant but differential impact of IOP. Clinicians must keep in mind the impact of large IOP fluctuation on the anterior corneal power.